Implementation of Geblek Processing Training for Micro, Small Medium Enterprise (MSMEs) in Kulon Progo Regency - Kusumo, Mahendro Prasetyo (Universitas Muhammadiyah Surakarta, 2024)
Cassava-based food processing techniques produced by MSMEs in Kulon Progo Regency are a healthy food choice for the community. The purpose of this community service is to improve the skills of MSMEs actors in processing cassava into healthy food. This community service is carried out using two methods, namely: 1) training and 2) assistance to geblek MSME actors in Kulon Progo Regency. The training was carried out for one hundred minutes by doctors and public health practitioners. The pre-test was carried out before the training, while the post-test was carried out after the training. During the training, the group discussion method was inserted to increase the understanding of MSMEs geblek actors in producing healthy food made from cassava. Assistance is carried out for two hours by a doctor to determine the level of skill of MSME actors in processing cassava into geblek. The pre-test and post-test scores for geblek processing training for MSMEs in Kulon Progo Regency showed an increase of 3.76%. The results of this community service have succeeded in changing the technique and composition of the geblek seasoning to be healthier. The change in seasonings that no longer use monosodium glutamate (MSG) and this way of serving without oil has a distinctive taste, namely: lighter and tastier. Geblek SMEs have skills in processing cassava into geblek with Non-MSG and Non-Oil spices. This innovation can be used as an alternative food for people with DM.